Bioinformatics Approach for the Selection of Single Nucleotide Polymorphisms of Genes - Adiga , Usha; Adiga , Shreyas; Rai , Tirthal; Honnalli , Neha Martin (Cutting Edge Research in Biology Vol. 4, 2023)
The aim of the chapter is to discuss the importance in silica analysis of genes using bioinformatics tools so as to explore the possible influence of mutations of these genes in linking the pathogenesis of various disease. Understanding the molecular underpinnings of a protein's function may be possible with knowledge about the native structure of the protein. The difference between proteins having empirically characterised structures and those without known structures is widening in the postgenomics era. An array of automated techniques known as bioinformatics tools that infer the structure of a protein from its amino acid sequence have emerged to deal with the deluge of data. These bioinformatics tools offer experimental biologists a collection of cutting-edge, thoroughly examined, user-friendly computational tools for protein structure prediction that will aid in the interpretation of their findings and the thoughtful design of new experiments. It can be concluded strongly that deleterious effects of mutations on genes as well as their reduced stability as predicted by the bioinformatics tools may influence the pathobiology of diseases.